Merdeka Belajar dalam Perspektif Islam - Chairunnisa Sahril Chaniago; Ahmad Darlis; Azlia Fasya Kintara; Jihan; Riswan; Asmalia (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to analyze the concepts of freedom to learn and freedom to learn from an Islamic perspective. The research method used is the library research method. This type of research uses a qualitative approach. The approach used is a descriptive study. The research results explain that Islam has never limited the learning process. This concept of freedom to learn was previously implemented by the Father of Indonesian Education, namely Ki Hadjar Dewantara. However, the concept he founded continues to undergo changes and follows changes along with changes in education ministers.